Between the “Structural” and the “Everyday”: Bridging Macro and Micro Perspectives in Comparative Urban Research - Nadine Appelhans; Sophie Schramm (Urban Planning, 2023)
The discussion around placing cities within a larger network of cities and the criteria by which they are assessed has recently gained new momentum. Consideration of Southern, disadvantaged, or “peripheral” geographies previously neglected in comparative approaches are now being considered and have opened up new perspectives on the wider urban context. This thematic issue, thereby, explores the practical challenges of how comparative urbanism across a broadening range of dissimilar places across the globe is handled. The collection of empirical studies presented will lay out the challenges and insights gained into applying comparative methodologies to the real-world context, thereby contributing to the advancement of empirical tools for complex and multi-scalar research environments.